Electrochemical synthesis of stabilizer-free silver nanoparticles with antibacterial properties - Awad, Mohammed Ahmed Hussein; Jamil, Yasmin M.S.; Al Maydama, Hussein M.A. (Thamar University Journal of Natural & Applied Sciences, 2024)
In this study, we present an electrochemical method for preparing silver nanoparticles (Ag NPs) powder using a metallic silver cathode and anode in an aqueous solution of doubled distilled water (DW) with a voltage of about 27 volts. The method does not involve the use of any chemical stabilizing agents. The synthesized Ag nanoparticles were characterized using X-ray diffraction (XRD) analysis and UV-visible Spectroscopy (UV). The experiment results indicate that the crystal structure of the Ag nanoparticles sample is face-centered cubic (FCC) structure the same as the bulk materials, the crystalline size distribution ranging from 15.86 to 21.30 nm, with an average crystalline size of about 18.7 nm obtained by XRD results. Colloidal silver-NPs with a grain size of 18.7 nm were produced at optimum conditions. A peak at 406 nm was obtained in UV-visible spectroscopy attributed to Ag NPs. In addition, the synthesized Ag nanoparticles revealed a tremendous antibacterial effect against pathogenic microorganisms.